Glycogen synthase kinase 3beta contributes to proliferation of arterial smooth muscle cells in pulmonary hypertension. - Piotr Sklepkiewicz; Ralph Theo Schermuly; Xia Tian; Hossein Ardeschir Ghofrani; Norbert Weissmann; Daniel Sedding; Tarek Kashour; Werner Seeger; Friedrich Grimminger; Soni Savai Pullamsetti (PLoS ONE, 2011)
Pulmonary arterial hypertension (PAH) is a rare progressive pulmonary vascular disorder associated with vascular remodeling and right heart failure. Vascular remodeling involves numerous signaling cascades governing pulmonary arterial smooth muscle cell (PASMC) proliferation, migration and differentiation. Glycogen synthase kinase 3beta (GSK3ß) is a serine/threonine kinase and can act as a downstream regulatory switch for numerous signaling pathways. Hence, we hypothesized that GSK3ß plays a crucial role in pulmonary vascular remodeling.All experiments were done with lung tissue or isolated PASMCs in a well-established monocrotaline (MCT)-induced PAH rat model. The mRNA expression of Wnt ligands (Wnt1, Wnt3a, Wnt5a), upstream Wnt signaling regulator genes (Frizzled Receptors 1, 2 and secreted Frizzled related protein sFRP-1) and canonical Wnt intracellular effectors (GSK3ß, Axin1) were assessed by real-time polymerase chain reaction and protein levels of GSK3ß, phospho-GSK3ß (ser 9) by western blotting and localization by immunohistochemistry. The role of GSK3ß in PASMCs proliferation was assessed by overexpression of wild-type GSK3ß (WT) and constitutively active GSK3ß S9A by [(3)H]-thymidine incorporation assay.Increased levels of total and phosphorylated GSK3ß (inhibitory phosphorylation) were observed in lungs and PASMCs isolated from MCT-induced PAH rats compared to controls. Further, stimulation of MCT-PASMCs with growth factors induced GSK3ß inactivation. Most importantly, treatment with the PDGFR inhibitor, Imatinib, attenuated PDGF-BB and FCS induced GSK3ß phosphorylation. Increased expression of GSK3ß observed in lungs and PASMC isolated from MCT-induced PAH rats was confirmed to be clinically relevant as the same observation was identified in human iPAH lung explants. Overexpression of GSK3ß significantly increased MCT-PASMCs proliferation by regulating ERK phosphorylation. Constitutive activation of GSK3ß (GSK3ß S9A, 9th serine replaced to alanine) inhibited MCT-PASMCs proliferation by decreasing ERK phosphorylation.This study supports a central role for GSK3ß in vascular remodeling processes and suggests a novel therapeutic opportunity for the treatment of PAH.